PERANCANGAN SISTEM KONTROL OTOMATIS LAMPU PENERANGAN PADA JANGKA WAKTU 24 JAM BERBASIS MIKROKONTROLER AT89S51 - Supardi, I Wyn; Wendri, Nyoman; Suarbawa, K.N. (BULETIN FISIKA; Vol 13 No 2 (2012): BULETIN FISIKA, 2012)
Has   successfully   created   a tool   Automatic   Lamp   Illumination   Control System based on Microcontroller   AT89S51 . This tool is used to turn on and dim the lights in the room. The series of Automatic Lamp Illumination Control system based on Microcontroller AT89S51 can  turn on lights automatically. NSL19_M51 LDR as a sensor. Lights lit up at 19.00 - 24.00 with the intensity of 020 lux, the intensity is 001 lux dimmest occurred at 06:00 hours. This is in accordance with the principle of LDR in a state where the light resistance of the LDR is smaller then a small voltage and the lights dimmed, if in the dark resistance of the LDRvoltage is large and bright lights.